Hurler’s disease presenting with quadriparesis and short stature - Sanadhya, Anuradha; Poswal, Lakhan; Gupta, Nitin; Sharma, Shivani; Yadav, Pooja (International Journal of Contemporary Pediatrics, 2021)
Mucopolysachharidosis are a broad spectrum of rare lysosomal storage disorder caused by deficiency of enzymes responsible for degradation of glycosaminoglycans (GAG), thus leading to accumulation of GAG in various body tissues leading to somatic and neurological manifestations. General phenotype includes coarse facies, corneal clouding, hepatosplenomegaly, dysostosis multiplex etc. Detailed clinical and radiological evaluation and identification of type of GAG excreted in urine narrows the diagnostic possibilities. Definitive diagnosis requires assay of specific enzymes in various tissues. Till date 14 different types of MPS including subtypes are identified. We report a case of 4 years old male child presented with short stature, spastic quadriparesis, bony abnormalities and hepatosplenomegaly without intellectual impairment.